Optimalisasi dan Evaluasi User Acceptance dan Usability dengan Penerapan Prototyping pada Aplikasi Manajemen Produk dan Pesanan - Ramadhani, Shumaya Resty; Afriyansyah, Muhammad Fajri (Jurnal Komputer Terapan, 2024)
The rapid development of information technology affects various aspects of life, including business. Disebut Kopi, a cafe founded in 2021, utilizes technology to handle online orders through third-party applications. However, business owners still do not feel they can maximize profits if they continue relying on partner applications for sales. Hence, an online ordering and business product management application was developed specifically for Disebut Kopi. This mobile and web-based application facilitates management and direct notification receipt for the business. The prototyping approach is used in the development of this application to ensure the participation of all users in gathering requirements, designing and iterating prototypes, and testing for evaluation. The selection of this method is based on the need to optimize system development so that the final product is accepted rapidly and smoothly without many changes at the end. With this approach, the owner, cashier, and customers of Disebut Kopi can actively provide feedback to ensure the application meets the needs during the design and development processes. Testing is carried out using Blackbox, Usability, and User Acceptance. Blackbox testing has 33 test cases that are 100% successful; user acceptance testing has 42 scenarios that are 100% accepted. In addition, the average usability testing result is 85.4%, which is included in the excellent category.